THE DIFFERENCES BETWEEN ENGLISH AND GERMAN ("Conference on Universal Science Research 2023", 2023)
This article presents that no one can deny that English and German are two widely used languages. While the former is a global language, the latter is second only to English in terms of number of speakers globally, with over 100 million speakers across every continent.  If you want to learn German, now is the perfect time due to globalization and high demand in the competitive job market. However, you may think that this is a difficult job but it is not.  If you speak English fluently, you will have no difficulty learning and mastering German. However, if you are a beginner, the process will be gradual. We've compiled a list of similarities between English and German, especially for you.